2018
DOI: 10.1080/13218719.2017.1412240
|View full text |Cite
|
Sign up to set email alerts
|

The Defendant with the Prison Tattoo: The Effect of Tattoos on Mock Jurors’ Perceptions

Abstract: Little is known about the potential for tattoos to bias how defendants are perceived. In Study 1, the participants (n D 30) viewed photographs of five men with a tattoo (prison or modern style) on the face and neck or arm. Individuals with prison-style tattoos were perceived more negatively, especially when the tattoos were located on the face and neck compared to the arm. In Study 2, participants (n D 120) were shown a photograph of a defendant who either had a prison-style tattoo or no tattoo, and read a sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Given the limits and exploratory nature of the present study, future researchers would be advised to address perceptions of psychological practitioners who are not White, thin, or considered conventionally attractive, addressing the potential effects of our confederate’s features. Additionally, changing the positioning of the tattoo may prove useful as studies have reported that tattoos on the neck or face were perceived more negatively than those on the arms (Brown et al, 2018). Future studies could also examine the content of participant tattoos and any potential effects of these content differences.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limits and exploratory nature of the present study, future researchers would be advised to address perceptions of psychological practitioners who are not White, thin, or considered conventionally attractive, addressing the potential effects of our confederate’s features. Additionally, changing the positioning of the tattoo may prove useful as studies have reported that tattoos on the neck or face were perceived more negatively than those on the arms (Brown et al, 2018). Future studies could also examine the content of participant tattoos and any potential effects of these content differences.…”
Section: Discussionmentioning
confidence: 99%
“…A person's physical appearance is one of the most recognizable and noticeable features to others in social interaction and communication. Previous studies have shown that one's physical appearance has a significant role in voting results 1 , sentencing decisions 2,3 and the success of executives 4 . In general, these findings suggest that a more attractive appearance is associated with more positive and lenient judgments by other people.…”
Section: Introductionmentioning
confidence: 99%
“…However, without quantitative evidence that is especially drawn from experimental studies, such an assumption is still tentative and not confirmed. In the literature, the majority of quantitative research on this topic comes from Western cultures [e.g., [1][2][3][4] ].…”
Section: Introductionmentioning
confidence: 99%